2014
DOI: 10.1186/scrt501
|View full text |Cite
|
Sign up to set email alerts
|

Synovial fluid and synovial membrane mesenchymal stem cells: latest discoveries and therapeutic perspectives

Abstract: Mesenchymal stem cells (MSCs) have the ability to differentiate into osteoblasts, chondroblasts, adipocytes, and even myoblasts. Most studies have focused on finding MSCs in different parts of the body for medical treatment. Every joint structure, including bone, joint fat, articular cartilage, and synovium, potentially contains resident MSCs. Recently, a progenitor cell population has been found in synovial fluid and showed similarities with both bone marrow and synovial membrane MSCs. Synovial fluid MSCs hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 52 publications
(85 reference statements)
1
81
0
Order By: Relevance
“…Later studies showed that the MSCs can be isolated from almost every tissue in the body, such as amniotic and synovial fluids, adipose, dental tissues, umbilical cord, peripheral bloods, dermis, brain, muscle and even tumors (Reynolds and Weiss 1992;Erices et al 2000;Seale and Rudnicki 2000;Zuk et al 2001;Roufosse et al 2004;De Coppi et al 2007;Haniffa et al 2007;Huang et al 2009;Yan et al 2012;de Sousa et al 2014). Although the MSCs have a big therapeutic potential, there are still many problems related to the sudden death of transplanted cells, migration out of transplanted organ, sedimentation into other organs causing unwanted differentiation, inflammation or even secondary cancers.…”
Section: Stem Cells For Tissue Regenerationmentioning
confidence: 97%
“…Later studies showed that the MSCs can be isolated from almost every tissue in the body, such as amniotic and synovial fluids, adipose, dental tissues, umbilical cord, peripheral bloods, dermis, brain, muscle and even tumors (Reynolds and Weiss 1992;Erices et al 2000;Seale and Rudnicki 2000;Zuk et al 2001;Roufosse et al 2004;De Coppi et al 2007;Haniffa et al 2007;Huang et al 2009;Yan et al 2012;de Sousa et al 2014). Although the MSCs have a big therapeutic potential, there are still many problems related to the sudden death of transplanted cells, migration out of transplanted organ, sedimentation into other organs causing unwanted differentiation, inflammation or even secondary cancers.…”
Section: Stem Cells For Tissue Regenerationmentioning
confidence: 97%
“…In general, stem cells are classified based on their source of origin as embryonic stem cells and tissue specific / adult stem cells. Recently, Shinya Yamanaka reported of creating pluripotent stem cells from terminally differentiated fibroblasts [2][3][4][5][6][7][8][9][10][11][12]. Stem cells are also classified based on their differentiation potential -totipotent (early progeny of the zygote up to the eight cell stage of the morula), pluripotent (Inner cell mass of embryo, epiblast), multi/oligopotent (Fetal tissues, membranes, placenta and adult stem cells), bipotent (lymphoid or myeloid stem cells) or unipotent (Muscle stem cells) [13,14].…”
Section: Stem Cellsmentioning
confidence: 99%
“…[1][2][3][8][9][10][11][12] These interventions include specific exercise programs, diets and nutritional supplements, and specific cell-based therapies including platelet-rich plasma (PRP) and stem cells as both mitigating agents in disease and the aging process. [102][103][104] The use of stem cells as immune modulators has shown tremendous promise. We now understand that the fate of the stem cells, which we introduce as therapies, is actually of secondary importance to the role they play in eliciting favorable changes in the immune response-primarily by generating anti-inflammatory and thus "antiaging" cytokines and chemokines (Table 1).…”
Section: Conclusion and Prospectsmentioning
confidence: 99%